Outcome of normal delivery with and without episiotomy in primiparous mothers in Sabzevar Mobini Hospital - Mitra Eftekhari Yazdi; Mostafa Rad; Behnaz Souizi; Sepideh Behrozinasab; Neda Mahdavifar; Marziyeh Torkmannejad Sabzevari (Mashhad University of Medical Sciences, 2021)
Introduction: Limited use of episiotomy and performing selective episiotomy versus conventional episiotomy has been recommended in various studies. But according to the statistics from developing countries, episiotomy is still the most common obstetric incision. The most common cause of episiotomy in low-risk mothers is maternal concern about severe perineal injuries. This study was performed with aim to compare perineal injuries in normal delivery of primiparous mothers with and without episiotomy. Methods: This descriptive-analytical study was performed by reviewing 3602 files of primiparous pregnant women who had a normal delivery in Sabzevar Obstetrics and Gynecology Hospital during 2017 and 2019. Data collection tool was a researcher-made checklist. The maternal demographic variables, active phase length, neonatal weight, neonatal head circumference, labor mobility, induction or non-induction with oxytocin, and exposure to analgesia, neonatal hospitalization in neonatal intensive care unit (NICU), neonatal death and the degree of perineal damage including grade 1, 2, 3 and 4 laceration. Data were analyzed by SPSS software (version 21) and Chi-square and regression tests. P<0.05 was considered statistically significant. Results: In the delivery group without episiotomy, 317 mothers (37.8%) had healthy perineum, 324 (38.5%) grade 1 laceration and 56 (6.6%) grade 2 laceration, but in the delivery group with episiotomy, 1302 (99.3%) had grade 2laceration. Chi-square test showed a significant difference between the two groups in terms of perineal injuries (P= 0.0001). The rate of severe perineal injuries was not significantly different in the delivery group with and without episiotomy (p> 0.05). The NICU admission was not significantly different between the two groups (p> 0.05).  Conclusion: Delivery without episiotomy in primiparous mothers who don't have risk factors for maternal diabetes, instrumental delivery and infant weight > 4000 g, does not increase severe perineal injuries.